Expansion of high-voltage overhead transmission lines to remote areas - Ibrahim Hasan Al-Kharsan; Ameer Al-khaykan; Hassan Falah Fakhruldeen (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
Delivering electrical energy to remote areas is one of the essential things in our modern world. Choosing the optimal route is one of the most critical factors contributing to reducing the power transmission system's cost. Other influencing factors such as the optimum alloy of the conductor wires are difficult to change, so only the aforementioned factor was adopted. In this paper, the optimized potential field algorithm is employed to determine the sub-optimum path that the transmission line should be installed. The best line for the towers is not necessarily the shortest or the cheapest one. Sometimes the best locations for the towers of the transmission lines coming according to the safety regards. It can be said that the best trajectory is a combination of several factors, including the length of the track in addition to other influencing factors depending on the work environment.